Desarrollo de una aplicación web para los procesos contables de los emprendimientos de las cajas solidarias de la ciudad de Latacunga. - Logacho Loya, Evelyn Alexandra (2020)
The present technological proposal is part of Strengthening popular and Solidarity Economy project of MYPIMES at Latacunga city, which consisted on web application development that will help the accounting processes of Solidarity Fund enterprises, where belonging members from solidarity funds register their businesses according to their needs. These companies generate income and expenses, where important information is obtained, which needs to be controlled by income and expense book (gains or losses), which it contribute to the internal administrative decisions of the business. In addition, the developed project was based on descriptive research, which allowed to define user requirements, bibliographic research, agreed to review information through primary sources, which served as theoretical basis for the proposed project. Together, information gathering techniques (interview) were used to identify the problem, define the main requirements and functionalities of the web application. For web application development, the Iterative-Incremental model and the unified modeling language (UML) were applied, developing nine fully functional iterations, each iteration completed the analysis, designing, coding and testing phases. Open Source tools were used, the PHP programming language and the MySQL database manager, the interpreted language JavaScript, cascading style sheets (CSS). In this way, it relies on the accounting management of the enterprises through the registration of purchases, production, sales and expenses, resulting in a final report that presents losses and gains in a business model that supports and contributes to the accounting processes that enterprises belonging to the Solidarity Funds carry out. In this way set objectives at the beginning of the project were fulfilled, resulting in a deliverable web application implemented at “Divino Niño” Solidarity Box of Latacunga city.